2016
DOI: 10.1111/ijlh.12482
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lymphocyte count as a prognostic marker in newly diagnosed multiple myeloma patients

Abstract: Absolute lymphocyte count as a prognostic marker in newly diagnosed multiple myeloma patients e56

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…Firstly, the peripheral blood ANC and AMC are precursor cell for myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM), respectively, which release growth and survival factors promoting tumor evasion of the host defense mechanisms ( 14 , 17 ). On the contrary, infiltrating lymphocytes were associated with favorable prognosis, as was recently shown in patients with MM ( 16 , 27 ). Therefore, NMLR will be a good surrogate marker of the real in vivo balance of immune system.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Firstly, the peripheral blood ANC and AMC are precursor cell for myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages (TAM), respectively, which release growth and survival factors promoting tumor evasion of the host defense mechanisms ( 14 , 17 ). On the contrary, infiltrating lymphocytes were associated with favorable prognosis, as was recently shown in patients with MM ( 16 , 27 ). Therefore, NMLR will be a good surrogate marker of the real in vivo balance of immune system.…”
Section: Discussionsupporting
confidence: 54%
“…How to evaluate the overall immune status of patients is an urgent problem in clinical practice. Recent researches reported that neutrophils inhibit the activation of T cells by reactive oxygen species, and monocytes as precursors of tumor-associated macrophages are closely related to the formation of MM immunosuppressive microenvironment, and absolute lymphocyte counts are independent prognostic factors for survival ( 14 16 ). Although there are some controversies, some evidence demonstrated that absolute neutrophils count (ANC) to the absolute lymphocyte count (ALC) ratio (NLR) and ALC to the absolute monocyte count (AMC) ratio (LMR), as immune state indicators of MM patients, play important roles in disease progression ( 14 , 17 , 18 ), which indicated that both neutrophils and monocytes are indispensable components in the complex immune microenvironment of MM and play different roles ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with lenalidomide provides an alternative choice for elderly patients and those unable to tolerate chemotherapy ( 16 , 17 ). In addition, prognostic factors, including peripheral lymphocytes and CRP, have been reported and were demonstrated to have a varying prognostic significance in traditional chemotherapy and novel drug protocols ( 4 , 5 , 18 , 19 ). This highlights the importance of discovering and identifying prognostic markers in MM for novel treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although previous studies had suggested ALC as a prognostic marker, recent investigations with the novel agents failed to demonstrate statistical significance. 12, 13 Our study is novel in that we show that the ALC/AMC is a more robust prognostic biomarker than ALC alone, as it assesses the relative strength of the host immune system to myeloma-induced immune dysfunction. To our knowledge, these findings have only once been suggested in a smaller Korean cohort 14 —our study in a larger cohort confirms and expands these findings in an immune context.…”
mentioning
confidence: 87%